Forecasting of Patients Condition in the Monitoring Medical Systems on the Example of Prostate Diseases - Goriacha, Veronica A.; Sokolov, Oleksandr Yu.; Ugryumova, Kateryna M.; Antonyan, Igor M.; Roshin, Yuri V.; Zelensky, Alexandr I.; Moshel, Fedor G.; Nalbandian, Taron A. (Journal of Education, Health and Sport, 2016)
Goriacha Veronica A., Sokolov Oleksandr Yu., Ugryumova Kateryna M., Antonyan Igor M., Roshin Yuri V., Zelensky Alexandr I., Moshel Fedor G., Nalbandian Taron A. Forecasting of Patients Condition in the Monitoring Medical Systems on the Example of Prostate Diseases. Journal of Education, Health and Sport. 2016;6(5):77-93. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51160 http://ojs.ukw.edu.pl/index.php/johs/article/view/3511 https://pbn.nauka.gov.pl/sedno-webapp/works/725671 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 05.05.2016. Forecasting of Patients Condition in the Monitoring Medical Systems on the Example of Prostate Diseases Goriacha Veronica A.1, Sokolov Oleksandr Yu.2, Ugryumova Kateryna M.1, Antonyan Igor M.3, Roshin Yuri V.3, Zelensky Alexandr I.3, Moshel Fedor G.3, Nalbandian Taron A.3 1Information technology department, National Aerospace University named by N. Ye. Zhukovsky “Kharkov Aviation Institute”, Ukraine 2Department of Informatics, Faculty of Physics, Astronomy and Informatics, Nicolaus Copernicus University, Grudzianska 5, 87-100, Torun, Poland 3Department of General and children's oncological urology, Medical Academy of Postgraduate Education Moscow Avenue 195, 61037, Kharkiv, Ukraine splaijna@gmail.com, osokolov@is.umk.pl, ukatya80@mail.ru, urology.edu.ua@gmail.com Abstract. The mathematical models and computational methods with implementing them applied information technology of decision support in monitoring medical system are proposed. The method of construction robust monitoring indices based diagnostic models for criteria quality assessment of the systems elements condition is described. The informativeness (significance) assessment method of the systems diagnosing models variables, obtained based on artificial neural networks (ANN) theory instrument is developed. The forecasting method of multivariate time series obtained on the monitoring indices based variables of the dynamic systems condition is developed. The method for solving the condition classification problem of the complex systems elements is improved. The decision support computer system in medical monitoring systems is developed. Application examples of the described methods on diagnosis of medical patients are presented. Keywords: Decision Support Software System, Reasoning Methods, computational methods, clinical medicine.